The effects of internet memes on formal speech and spoken grammar among UTAR Undergraduates - Seow, Sun Jun (2021)
Internet memes have grown in popularity amongst internet users and its effects on language, especially its role in introducing new yet informal vocabulary, sparked concerns on its possible deterioration on language. This research is done in response to whether it affects spoken grammar and choice of words in formal settings, particularly internet slang that derive from internet memes. 10 participants were tasked to give a formal impromptu speech which were recorded, transcribed and analysed for grammatical errors and use of internet slang. These were then compared with how often they look at internet memes as stated by said participants in a semi-structured interview that followed. Analysis showed that there was no relation between internet memes and the 2 variables stated. However, findings suggested that grammatical errors were instead caused by the speakers’ own skills, and the absence of internet slang in said speeches were the result of the speakers’ context consciousness, that they were aware of the inappropriate use of informal words in formal settings.